THE EFFECT OF WORK ENVIRONMENT, ACHIEVEMENT MOTIVATION, AND WORK PERFORMANCE ON THE QUALITY OF SERVICE PROVIDED BY EMPLOYEES OF THE SUNGAI PENUH CITY LIBRARY AND ARCHIVES DEPARTMENT - Syafrizal, Doni; Regen, Ronal (Qawwam : The Leader's Writing, 2026)
This study aims to analyze the influence of Work Environment, Achievement Motivation, and Work Competence on Service Quality among employees at the Library and Archives Department of Sungai Penuh City, given the background of still-low achievement motivation, limited work environment facilities, and the need to improve employees technical skills. The study employed a quantitative method through a questionnaire survey, and the data were analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R ) via IBM SPSS 26.0. The results indicate that, individually, each of the variables Work Environment, Motivation to Excel, and Work Competence has a positive and significant effect on service quality. Simultaneously, these three variables also have a significant combined effect with an R value of 0.797, indicating that 79.7% of the variation in service quality is explained by these three factors. In conclusion, employee service quality is influenced by a combination of a conducive work environment, high achievement motivation, and adequate work competence; therefore, efforts to improve service quality must be carried out in an integrated manner through the development of the work environment, the enhancement of motivation, and the continuous improvement of employee competencies.